2018
DOI: 10.1111/ejn.14215
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic afferents to prefrontal cortices from ventral motor nuclei in decision‐making

Abstract: The focus of this literature review is on the three interacting brain areas that participate in decision‐making: basal ganglia, ventral motor thalamic nuclei, and medial prefrontal cortex, with an emphasis on the participation of the ventromedial and ventral anterior motor thalamic nuclei in prefrontal cortical function. Apart from a defining input from the mediodorsal thalamus, the prefrontal cortex receives inputs from ventral motor thalamic nuclei that combine to mediate typical prefrontal functions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 172 publications
2
25
0
Order By: Relevance
“…It is unclear whether the cerebellum projects to the mediodorsal thalamic nuclei, which are known to provide the main thalamic inputs to the prefrontal cortex [109,110]. Recently, reciprocal connectivity between the prefrontal cortex and ventral thalamic nuclei (specifically ventromedial) has been shown [109,111,112]. The second pathway involves DCN projections to the ventral tegmental area (VTA) which, in turn, send dopaminergic fibers to the prefrontal cortex [113].…”
Section: Non-sensorimotor Functionsmentioning
confidence: 99%
“…It is unclear whether the cerebellum projects to the mediodorsal thalamic nuclei, which are known to provide the main thalamic inputs to the prefrontal cortex [109,110]. Recently, reciprocal connectivity between the prefrontal cortex and ventral thalamic nuclei (specifically ventromedial) has been shown [109,111,112]. The second pathway involves DCN projections to the ventral tegmental area (VTA) which, in turn, send dopaminergic fibers to the prefrontal cortex [113].…”
Section: Non-sensorimotor Functionsmentioning
confidence: 99%
“…Nevertheless, if vS1 is not required for sensory decision making, one alternative explanation for the observed results is that neuronal activity in the somatosensory cortex and behavioral outcomes may both be modulated by state independently. State may affect behavioral outcomes via subcortical processing circuits such as brainstem (Tsunematsu et al, 2020) and thalamic nuclei (Sieveritz et al, 2019) and superior colliculus (Crapse et al, 2018;Wang et al, 2020) . The state-modulations in subcortical circuits may then be transmitted to sensory cortex producing choice-related activity in vS1 (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ventromedial (VM) thalamic projection neurons extensively innervate cortical layer I (Herkenham 1979 ; Arbuthnott et al 1990 ). Biane et al ( 2016 ) optically stimulated axon terminals from the ventral motor thalamic nuclei, i.e., the ventromedial, ventrolateral and ventral anterior thalamic nuclei (Sieveritz et al 2019 ), and recorded monosynaptic responses ex-vivo in rat primary motor cortex. After skilled grasp training, response amplitude of layer V neurons that control grasp related muscles in the distal forelimb was significantly larger compared to layer V neurons that control muscles in the proximal forelimb (Biane et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral photoinhibition of ALM or VM activity during a delay phase, prior to making a response, impairs the performance of animals on a sensory discrimination task, highlighting the importance of this thalamocortical loop in planning a response (Guo et al 2017 ). We previously suggested that VM projection neurons to other frontal cortical areas may be involved in regulating behaviors associated with those frontal cortical areas (Sieveritz et al 2019 ). For example, optogenetic manipulation of prelimbic corticostriatal neurons in cost–benefit decision-making alters the preference of rats for a high cost-high reward option as compared to a low cost-low reward option, even though perception of cost and reward values remains unchanged (Friedman et al 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%